Excavation, Capture, Collection, and Creation: Computer Scientists' Metaphors for Eliciting Human Expertise. - LaFrance, Marianne (Metaphor & Symbolic Activity, 1992)
This article describes how practitioners in artificial intelligence describe the transfer of expertise from human experts to computer programs called expert systems. These programs are designed to mimic human problem-solving expertise in specific domains. The metaphors are drawn from several sources that describe how such systems are built and also from interviews with veteran expert-system programmers. Four central metaphors are identified: "EXCAVATION," "CAPTURE," "COLLECTION," and "CREATION. "In each case, the metaphor is described and examples are provided. Discussion centers on showing how the respective metaphors grew out of successive stages in the development of this computer technology and how they in turn have contributed to subsequent development. Finally, note is made of the "downside" of the metaphors that have been devised to describe the transfer of human expertise.